Letter (copy) : Report on Spain - Citrine, Walter, 1887-1983
011-0060-001 WMC/WJB/AC/946 International 13th August, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, REPORT ON SPAIN. You will recollect that at the London Conference in March last, it was decided that the two Internationals should publish "documents on the origin and character of the struggle in Spain." You were going to talk this matter over with Comrade Adler. Will you kindly let me know whether you have had an opportunity of doing this, and whether you have come to any decision about preparing and publishing a joint report on the lines of the resolution. Yours faithfully, General Secretary. 292/946/11/60